Service Quality Dimensions in Pay TV Industry: A Preliminary Study - Norazryana Mat Dawi; Ahmad Jusoh; Khalil Md Nor; Muhammad Imran Qureshi (International Review of Management and Marketing, 2016)
Pay TV industry has been experiencing a considerably high growth rate in terms of revenues and subscribers Technological advancement in pay TV services industry inflicts the demands for higher service quality for competitiveness and business success. The increasing demand in pay TV service offerings has led operators to become competitive. However, limited literature on the instruments to measure service quality in the context of pay TV services is available. A thorough review of literature in service quality exposed negligible efforts to develop instrument to measure service quality in pay TV setting. Thus, through an extensive review of past literature, the present study develops an instrument to explore service quality dimensions in pay TV setting. The current study identified seven service quality dimensions in pay TV setting. These dimensions are tangibles, reliability, content quality, customer service, price, convenience and interactivity. Furthermore, reliability of these dimensions was tested through the pilot survey from 34 respondents. Results revels the value of cronbach’s alpha of all dimensions were higher than 0.60, this indicates that all service quality dimensions in the context of pay TV were reliable